PENGARUH LATIHAN MULTIDIRECTIONAL HURDLE JUMPS TERHADAP DAYA LEDAK OTOT TUNGKAI PEMAIN SEPAKBOLA SMA PGRI PEKANBARU - Yudhi Fratama Fambudi Fratama Fambudi; Slamet '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The issues raised in this study is " What is the effect of exercise multidirectional hurdle jumps toward muscular power at the football players senior high school PGRI Pekanbaru.?" This research is experimental research that aims to find out the effect of exercise multidirectional hurdle jumps toward muscular power at the footbal players senior high school PGRI Pekanbaru. The population this experimen all football players senior high school PGRI Pekanbaru. This study used total sampling all football players be sampel. Were obtained and collected through the initial test and final test before and after multidirectional hurdle jumps using a meansuring tool that is standing broad jump. The method of processing data using descriptive statistics calculations and to test the hypothesis using the t test. The hypothesis proposed in this study is the effect of exercise multidirectional hurdle jumps to the muscular power at football players senior high school PGRI Pekanbaru. The results of the t test produced 8,86 and 1,740 ttable at the significant level of 0.05. Means > t table. It can be concluded that Ha can be Received.This gives the conclusion that there is a significant effect of exercise multidirectional hurdle jumps to the muscular power at the footbal players senior high school PGRI Pekanbaru. Key Words:  Exercise multidirectional hurdle jumps muscular power